2001
DOI: 10.1089/152460901750067142
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Healthy Minority Women into Community-Based Longitudinal Research

Abstract: This report examines the impact of individualized, population-based recruitment and retention approaches on the development of a subject pool, enrollment, and retention at 12 months of healthy, community-based women in three ethnic groups: African Americans, non-Hispanic European Americans, and Mexicans/Central Americans. Of 722 women contacted and screened, 346 (48%) were eligible and consented to participate. Attrition at 12 months was low (10%) compared with other published reports. The largest group of pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
177
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(191 citation statements)
references
References 10 publications
14
177
0
Order By: Relevance
“…However, women who were recruited from community events were more likely to be older, a member of a minority group, with lower incomes, and with a self-reported disability. This is comparable with other studies that documented higher yields of racial and ethnic participants when face-to-face contact methods were used (37,46,(48)(49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 89%
“…However, women who were recruited from community events were more likely to be older, a member of a minority group, with lower incomes, and with a self-reported disability. This is comparable with other studies that documented higher yields of racial and ethnic participants when face-to-face contact methods were used (37,46,(48)(49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 89%
“…This finding holds true for both Chinese and Korean speakers, regardless of whether the recruiters had strong ties to the ethnic community. These findings echoed prior recruitment research that shows media broadcasting or printed materials reach a larger portion of the general population (Appel et al 1999;Gilliss et al 2001;McLean and Campbell 2003), and that word of mouth was effective for recruiting Hispanics who spoke little or no English . We also found that the differences of screener completion rates across the recruitment methods were statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…Referrals or word of mouth seemed to work better for identifying minority participants who qualify for the study. However, they reached a far smaller number of potential participants (Bistricky et al 2010;Gilliss et al 2001;Wisdom et al 2002).…”
Section: Related Researchmentioning
confidence: 99%
“…The recruitment strategy used evidence‐based techniques for hard to reach and minority groups: culturally sensitive study materials, multiple recruitment strategies and incentives 37, 38, 39, 40, 41, 42, 43. Two recruitment strategies were assessed: recruitment from general practice registers and by a community outreach strategy.…”
Section: Methodsmentioning
confidence: 99%